2014
DOI: 10.1152/ajplung.00012.2014
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead Box F1 represses cell growth and inhibits COL1 and ARPC2 expression in lung fibroblasts in vitro

Abstract: Aberrant expression of master phenotype regulators or alterations in their downstream pathways in lung fibroblasts may play a central role in idiopathic pulmonary fibrosis (IPF). Interrogating IPF fibroblast transcriptome datasets, we identified Forkhead Box F1 (FOXF1), a DNA-binding protein required for lung development, as a candidate actor in IPF. Thus we determined FOXF1 expression levels in fibroblasts cultured from normal or IPF lungs in vitro, and explored FOXF1 functions in these cells using transient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 49 publications
(39 reference statements)
1
27
0
Order By: Relevance
“…control lungs was verified histologically as described previously (15,16 Experiments with matriptase hypomorphic mice were littermate controlled from mice generated from heterozygous crosses (18). The bleomycin murine model of pulmonary fibrosis was set up as described previously (19).…”
Section: Original Articlementioning
confidence: 99%
“…control lungs was verified histologically as described previously (15,16 Experiments with matriptase hypomorphic mice were littermate controlled from mice generated from heterozygous crosses (18). The bleomycin murine model of pulmonary fibrosis was set up as described previously (19).…”
Section: Original Articlementioning
confidence: 99%
“…Ghouleh et al demonstrated that ARPC2 participated in promoting smooth muscle cell migration [6]. Melboucy-Belkhir et al determined that ARPC2 was regulated by Forkhead box F1 (FOXF1) and might be involved in cell growth of lung fibroblasts [12]. To date, there is no publication that documents the relation between ARPC2 and tumor proliferation or invasion.…”
Section: Introductionmentioning
confidence: 99%
“…To this aim, multiple experiments comparing the transcriptome of IPF lung fibroblasts to normal lung fibroblasts using RNA microarrays were previously published [5,6,7,8]. These studies yielded conflicting results with little overlap [9], most likely because of the generally small study size, of the high variability inherent to clinical samples, and of possible center-related bias. We hypothesized that combining these individual studies into a single meta-analysis may allow for the identification of robust alterations of mRNA expression in IPF fibroblasts, with the potential to reveal or confirm pathogenic mechanisms and therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%